La refonte d'un référentiel de compétences : processus et enjeux - Alexia Stumpf
This article is about the process of reworking the skills' repository in a University of Teacher Education in Switzerland who are training for teaching in high or grammar schools. In a first time, once the main notions have been defined, we are presenting the questions at the origin of this research and the methodology used to achieve the process.In a second time, we are highlighting the more professionalizing aspects of the new repository and pointing out ideas that can lead to a better harmonization with the curricula and more adequacy between the different levels that render the notion of professionalization. They are based on a compared analysis of both repositories.